2017
DOI: 10.1093/intqhc/mzx011
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned readmissions within 30 days after discharge: improving quality through easy prediction

Abstract: The model can be easily applied when discharging patients who have been hospitalized after an access to the Emergency Department to predict the risk of rehospitalization within 30 days. The prediction can be used to activate focused hospital-primary care transitional interventions. The model has to be validated first in order to be implemented in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 8 publications
0
11
1
4
Order By: Relevance
“…According to our estimates, women were at higher risk of readmission and this finding was in contrast to other studies using single-center settings, where no significant effect of gender was identified [9,37,38,39]. Moreover, according to a systematic review on risk prediction models for readmission, the gender variable in most studies “did not contribute enough to be included in the final model” [6].…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…According to our estimates, women were at higher risk of readmission and this finding was in contrast to other studies using single-center settings, where no significant effect of gender was identified [9,37,38,39]. Moreover, according to a systematic review on risk prediction models for readmission, the gender variable in most studies “did not contribute enough to be included in the final model” [6].…”
Section: Discussioncontrasting
confidence: 84%
“…An American study based on data from a university hospital in California analyzed 10,359 admissions (2006–2008) discharged from general medicine service with RaR of 17.0% [37]. Another recent Italian study identified the rate of unplanned readmissions as 11.6% at Pisa University Hospital (data for 5388 admissions in 2012) [38]. A prospective cohort study from a single Belgian university hospital (data for years 2011–2012) reported a RaR of 18.6% for emergency department patients aged >75 years [39].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the underlying deep learning logic and its findings are in line with the existing clinical literature. Prior research has found that the presence of comorbidities, such as diabetes, heart failure, renal failure, and pneumonia, are the main risk factors resulting in unplanned readmissions [41,42]. These disorders are shown to have strong correlations with abnormal features identified by our model [17].…”
Section: Discussionmentioning
confidence: 77%
“…Second, over recent years, the lengths of hospital admissions have reduced [35] and so patients are increasingly going home with ongoing care needs such as wound care management or medication monitoring. Collecting data during the initial post-discharge period when patients may still be unwell and/or particularly vulnerable to hospital readmissions [36] may impact our CRF return rates. Third, retention and attrition will need to be monitored as follow-ups are being conducted up to 90-days post-discharge.…”
Section: Post-discharge Follow-upsmentioning
confidence: 99%